The Effect of Problem-Based Learning and Discovery Learning on Students' Critical and Creative Thinking Skills on Material of Islamic Kingdom Development - Muhammad Eko Subagtio; Nasution Nasution; M. Jacky (Universitas Negeri Surabaya, 2021)
This study aims to determine: 1) the difference in the effect of problem based learning and discovery learning on students' critical and creative thinking skills, 2) the effect of problem based learning and discovery learning on students' critical and creative thinking skills simultaneously. This type of research is a quasi-experimental design with a nonequivalent comparison-group design. Collecting data using pre-test and post-test in the experimental class I and II. The data analysis technique used the independent sample test and Manova test with the help of the IBMM SPSS Statistics version 23 application. The results of the independent sample test showed that the critical thinking variable obtained a score of tcount 2.180 > ttable 1.996 with df. 66 and creative thinking variable with a score of tcount 2.103 > ttable 1.996. Based on these results, it can be concluded that there are different effects on critical and creative thinking skills. In the Manova test results obtained a significance of 0.26 <0.05 so that it can be concluded that there is an effect on critical and creative thinking skills simultaneously on the material for the development of the Islamic empire. The comparison results show that discovery learning has more influence on critical and creative thinking skills with an n-gain of 0.49, compared to problem-based learning with an n-gain of 0.41.